Physiological complexity of gait between regular and non-exercisers with Parkinson's disease. (August 2019) - Combs-Miller, Stephanie A.; Dugan, Eric L.; Beachy, Ann; Derby, Brook B.; Hosinski, Alicia L.; Robbins, Kristen
Abstract: Background: Physiological complexity represents overall health of a system and its underlying capacity to adapt to stresses. The primary purpose of this study was to determine if physiological complexity of gait both ON and OFF anti-Parkinson medication differed between regular and non-exercisers with Parkinson's disease. Methods: Twenty participants with idiopathic Parkinson's disease were enrolled in this cross-sectional study (regular exercisers n  = 10, non-exercisers n = 10). Two data collection sessions were completed during a single visit, first after a 12-hour overnight withdrawal from anti-Parkinson medications (OFF), and again one-hour after taking anti-Parkinson medications (ON). During each session participants completed a 2-minute walking task at their preferred pace while wearing wireless inertial measurement units on each lower extremity segment (thigh, shank, foot). Multivariate multiscale entropy was calculated from the tri-axial accelerometer signals and converted to a complexity index for analysis. Findings: Regular exercisers demonstrated significantly higher complexity indices ON and OFF anti-Parkinson medications compared to non-exercisers (ON F  = 3.84 P  = 0.02; OFF F  = 3.61, P  < 0.03). Regular exercisers did not significantly differ in complexity between OFF and ON states (most affected leg F  = 0.15 P  = 0.71; least affected leg F  = 0.30 P  = 0.60), but non-exercisers demonstrated significantly decreased complexity in the least affected leg OFF anti-Parkinson medications ( F  = 5.17 P  < 0.04). Interpretation: Enhanced gait complexity in the regular exercisers may indicate that ongoing exercise is a key ingredient contributing to health in persons with Parkinson's disease. Exercising on a regular basis with Parkinson's disease may augment one's ability to adapt to barriers encountered during gait regardless of medication state. Highlights: Gait complexity is greater in exercisers regardless of being ON or OFF medications. Persons with Parkinson's who exercise have better capacity to adapt their gait. Anti-Parkinson medications did not alter gait complexity in regular exercisers. Anti-Parkinson medications improved gait complexity in non-exercisers.